Involvement of protein tyrosine phosphatases BcPtpA and BcPtpB in regulation of vegetative development, virulence and multi-stress tolerance in Botrytis cinerea. - Qianqian Yang; Fangwei Yu; Yanni Yin; Zhonghua Ma (PLoS ONE, 2013)
Tyrosine phosphorylation and dephosphorylation have emerged as fundamentally important mechanisms of signal transduction and regulation in eukaryotic cells, governing many processes, but little has been known about their functions in filamentous fungi. In this study, we deleted two putative protein tyrosine phosphatase (PTP) genes (BcPTPA and BcPTPB) in Botrytis cinerea, encoding the orthologs of Saccharomyces cerevisiae Ptp2 and Ptp3, respectively. Although BcPtpA and BcPtpB have opposite functions in conidiation, they are essential for sclerotial formation in B. cinerea. BcPTPA and BcPTPB deletion mutants ΔBcPtpA-10 and ΔBcPtpB-4 showed significantly increased sensitivity to osmotic and oxidative stresses, and to cell wall damaging agents. Inoculation tests showed that both mutants exhibited dramatically decreased virulence on tomato leaves, apples and grapes. In S. cerevisiae, it has been shown that Ptp2 and Ptp3 negatively regulate the high-osmolarity glycerol (HOG) pathway and the cell wall integrity (CWI) pathway. Although both BcPtpA and BcPtpB were able to inactive Hog1 and Mpk1 in S. cerevisiae, in contrast to S. cerevisiae, they positively regulate phosphorylation of BcSak1 (the homologue of Hog1) and BcBmp3 (the homologue of Mpk1) in B. cinerea under stress conditions. These results demonstrated that functions of PTPs in B. cinerea are different from those in S. cerevisiae, and BcPtpA and BcPtpB play important roles in regulation of vegetative development, virulence and in adaptation to oxidative, osmotic and cell-wall damage stresses in B. cinerea.